Fit to win Singapore 2014 - Chin, Yi Xin (2014)
Fit To Win is a Nanyang Technological University student-initiated health promotion campaign. It is the first social weight loss challenge in Singapore that utilises an incentive-based system to motivate participants to engage in healthy behaviors, such as increasing their level of physical activity. The target audience of the campaign is made up of young adults aged 20 – 35 years old. The campaign will be driven via online and social media, as well as main offline events and activities. This report documents the entire campaign, and is sectioned into formative research, strategic communications campaign, sponsorships, campaign execution, public relations plan, expenditure, evaluation, discussion and lastly conclusion. The campaign was found to be effective in motivating participants to engage in physical activity and in changing participants’ attitudes towards exercising. Limitations and improvements were discussed for future considerations and sustainability of the campaign.